Effect of Knee Angle Perception on Electrophysiological Response in Sportsmen - (:unkn) unknown (IEEE, 2019)
Proprioception sense is an important issue in sports. This system works for the exchange of information from muscle to brain and brain to muscle. During this transmission, electrical impulses occur in the brain tissue and these signals are used for the brain computer interaction applications. In the concept of this study, during the perception of different knee angles (15, 30, 60 and 90 degrees), EEG signals are collected while the eyes of the subjects were closed. EEG signals are collected from 14 electrodes from 32 subjects. There were no significant differences between the angles and the brain responses. It was observed that electrical activity measured from different spatial locations of the scalp surface were found to significantly differentiate among the frequency bands.
Keywords: Proprioception; knee angle; Electroencephalography (EEG)